Brain Hemispheres Swap Dominance for Processing Semantically Meaningful Pitch - Wang, Xiao-Dong; Xu, Hong; Yuan, Zhen; Luo, Hao; Wang, Ming; Li, Hua-Wei; Chen, Lin (Frontiers in Human Neuroscience, 2021)
The question of what determines brain laterality for auditory cognitive processing is unresolved. Here, we demonstrate a swap of hemisphere dominance from right to left during semantic interpretation of Chinese lexical tones in native speakers using simultaneously recorded mismatch negativity response and behavioural reaction time during dichotic listening judgment. The mismatch negativity, which is a brain wave response and indexes auditory processing at an early stage, indicated right hemisphere dominance. In contrast, the behavioural reaction time, which reflects auditory processing at a later stage, indicated a right ear listening advantage, or left hemisphere dominance. The observed swap of hemisphere dominance would not occur when the lexical tone was substituted with a meaningless pure tone. This swap reveals dependence of hemisphere labor division initially on acoustic and then on functional cues of auditory inputs in the processing from sound to meaning.